Pengaruh Jenis Ektrakurikuler Dan Kedisiplinan Siswa Madrasah Tsanawiyah Almaarif 02 Singosari Terhadap Prestasi Belajar Pasca Covid-19 - Hidayati, suci; Mustaghfiroh, Yuliana Nur; Harini, Sri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research originated from the problem of declining learning achievement of students of MTs Almaarif 02 Singosari Malang after the Covid-19 pandemic. One of the indicators of the decline in student learning achievement is the odd Midterm Test (UTS) results in 2021/2022 which was carried out in October 2021. From 25 students who took part in UTS, KKM scores were obtained that did not meet the completion of learning. In the results of the UTS odd semester 2021/2022 which was held in September 2021, data was obtained that the average score of grade 7 students was still below the KKM score in each field of study. This study aims to determine the influence of types of extracurricular activities and discipline on the learning achievement of students of MTs. Almaarif 02 Singosari Malang for the 2021/2022 academic year. The method used to analyze the data used logit regression with 25 active students. Indicators for determining student learning achievement using a scale of likes 1-4. The results showed that in Model logistic regression the level of influence of extracurricular types and discipline was at a fairly complete and complete level with mathematical models: [Y1=2]=10.356+0.557 X1+0.355 X2 dan It can be concluded that extracurricular types have a significant influence on learning achievement with a significance value of 0.069 less than the error level of 10% and student discipline variables do not have a significant influence on learning achievement in grade 7 students of MTs. Almaarif Singosari 02 Malang.